Yoga as Complementary Care for Young People Placed in Juvenile Institutions—A Study Plan - Kerekes, Nóra (Frontiers in Psychiatry, 2021)
Recent studies have established yoga practice as a mainstream complementary clinical tool within correctional environments. It is shown that regular yoga practice is coupled with improved impulse control, sustained attention, attenuated antisocial and self-harm behaviors, reduced stress, and psychological distress. No academic research until now has provided evidence of mental health benefits of yoga for institutionalized young people. In Sweden, each year more than thousand adolescents receive compulsory care at juvenile institutions run by the Swedish National Board of Institutional Care. These young people are characterized by substance abuse, aggressive and antisocial behaviors, high frequency of self-harm, and the experience of abuse. Most of them manifest attention problems, depression, anxiety, and impulsivity. They have a dramatically increased risk for recidivistic criminal behavior, continuous medical, and social care and untimely death. The present study plan aims at evaluating, with previously validated psychological measures, in a quasi-experimental design, the effects of yoga practice for institutionalized adolescents. Adolescents' experiences of participating in yoga practice will also be assessed by semi-structured individual interviews. Ethical approval was given by the Swedish Ethical Review Authority. It is hypothesized that yoga practice (in combination with the standard treatment within institutional care) will reduce institutionalized adolescents' aggression, antisocial behavior, anxiety, depression, and negative affect, and increase their cognitive flexibility (in the form of increased impulse control).